Strategi Pengelolaan Desa Minggirsari sebagai Desa Wisata Alam Ramah Lingkungan - Hesty Puspita Sari; Anita Reta Kusuma Wijayanti (Prosiding ESEC, 2023)
Bordering the Brantas River, Minggirsari Village develops the tourism sector through exploiting local natural potential. Outdoor activities are the main attraction for Minggirsari Village tourism such as: Hanging out at Ban Kali Brantas, Rafting on the Brantas River, Glamping tours on the banks of the Brantas River and culinary dining at Papringan. To develop tourism potential, Minggirsari Village does not only present natural activities but implements a mature strategy and planning. So, this study aims to determine the management strategy of Minggirsari Village as an environmentally friendly natural tourism village. Researchers conducted observations and interviews with the managers of the Minggirsari Tourism Village to obtain information. Qualitative descriptive method was applied in this research by using SWOT analysis and strategy. With its natural potential, Minggirsari Village is able to create Village-based tourism as one of the strategies for managing eco-friendly nature tourism villages